РАЗВИТИЕ ФИЗИЧЕСКИХ КАЧЕСТВ В ВОЛЕЙБОЛЕ - Ниязов, А.Т.; Баватов, Ф.; Толыбаева, А.А. (SCIENCE and SOCIETY, 2023)
This article describes the method of developing physical qualities in volleyball players with which you can achieve high results in the game, volleyball as part of physical education is quite a popular and spectacular sport, the article describes the role of volleyball classes for students of higher educational institutions.